Acute kidney injury in the patient with cancer - Mitchell H. Rosner; Mark A. Perazella (The Korean Society of Nephrology, 2019)
Dramatic advances in the care of patients with cancer have led to significant improvement in outcomes and survival. However, renal manifestations of the underlying cancer as well as the effects of anti-neoplastic therapies leave patients with significant morbidity and chronic kidney disease risks. The most common renal manifestations associated with cancer include acute kidney injury (AKI) in the setting of multiple myeloma, tumor lysis syndrome, post-hematopoietic stem cell therapy, and AKI associated with chemotherapy. Knowledge of specific risk factors, modification of risk and careful attention to rapid AKI diagnosis are critical for improving outcomes.